Characterisation of lanthanum cobalt magnesium oxide prepared by a co-precipitation method - Parkash O.; Kumar R.; Prasad C.D.; Kumar D. (My University, 2025)
Samples with x=0.20, 0.30 and 0.50 in the system LaCo1-xMgxO3 have been prepared by a co-precipitation technique. These have orthorhombic structure and are oxygen deficient. The Seebeck coefficient initially increases as the temperature increases up to a particular value, then decreases, and finally becomes independent of temperature for all three samples. The resistivity increases with x, indicating that the conduction is mainly due to cobalt ions. The compositions with x=0.20 and 0.30 show frequency-independent AC conductivity at all temperatures greater than 300 K while for the composition with x=0.50 frequency-dependent AC conductivity is observed below 450 K. © 1988 IOP Publishing Ltd.